2016
DOI: 10.1002/cplu.201500558
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Radical/Metal Ion Adducts: A Gas‐Phase Structural Elucidation and Reactivity Study

Abstract: The formation and investigation of sulfur‐based cysteine radicals cationized by a group 1A metal ion or Ag+ in the gas phase are reported. Gas‐phase ion–molecule reactions (IMR) and infrared multiple‐photon dissociation (IRMPD) spectroscopy revealed that the Li+, Na+, and K+ adducts of the cysteine radical remain S‐based radicals as initially formed. Theoretical calculations for the three alkali metal ions found that the lowest‐energy isomers are Cα‐based radicals, but they are not observed experimentally owin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…However, [c 1 + Na–H] + ions are detected in MS/MS spectra of two sodiated peptide ions and as a base peak is produced by [Ac‐QK‐NH 2 + Na] + . Dissociation pathways of alkali metal‐associated peptides have been widely studied and often give particular ions regulated by charge‐remote reactions due to the ion structure stabilized by multidentate coordination and the absence of mobile protons …”
Section: Resultsmentioning
confidence: 99%
“…However, [c 1 + Na–H] + ions are detected in MS/MS spectra of two sodiated peptide ions and as a base peak is produced by [Ac‐QK‐NH 2 + Na] + . Dissociation pathways of alkali metal‐associated peptides have been widely studied and often give particular ions regulated by charge‐remote reactions due to the ion structure stabilized by multidentate coordination and the absence of mobile protons …”
Section: Resultsmentioning
confidence: 99%
“…Subsequent systematic studies have been made of the interconversion of cysteine‐containing peptides between sulfur‐centered cysteinyl radical and α‐carbon backbone‐centered radical using the GCG system; the energy barrier for the conversion between [G α • CG] + and [GC S • G] + is 41.5 kcal/mol, 38.1 kcal/mol between [GC α • G] + and [GC S • G] + , and 36.5 kcal/mol between [GCG α • ] + and [GC S • G] + . Metal ions also lower barrier for S to α‐carbon conversion by hydrogen atom transfer in Cys and Hcy radicals . For GRL/I systems, the basic arginine residues can again facilitate the tautomerizations between [G α • R(L/I)] + and [GR(L/I) γ • ] + via a 1,9‐HAT directly between the γ‐carbon atom of the leucine or isoleucine residue and the N‐terminal α‐carbon atom.…”
Section: Interconversion Among Various Tautomers Of Peptide Radical Cmentioning
confidence: 99%
“…In contrast, facile tautomeric interconversions have been observed for sodiated analogs . Hopkinson and Ryzhov and co‐workers have reported that alkali metal ions and silver ion can, respectively, also assist the thiyl‐to‐α‐carbon radical conversion in homocysteine radical and cysteine radical . O'Hair and co‐workers examined the CID of ternary [Cu II (terpy)(TMPP−M)] 2+ complexes, where TMPP−M represents a peptide (M) modified by conversion of the N‐terminal amino group to a [tris(2,4,6‐trimethoxyphenyl)phosphonium]acetamide (TMPP) fixed‐charge derivative .…”
Section: Interconversion Among Various Tautomers Of Peptide Radical Cmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Gas phase experiments using collision induced dissociation coupled to ion trap mass spectrometry isrepresent another useful approach to generate thiyl radicals by dissociation of S-nitrosylated homocysteine compounds. [18,19] Light can also be used to generate cysteine radicals from modified peptides in the gas phase. [20] A similar approach was used by Julian et al with quinone-substituted cysteines, although, in this latter case, the photo-induced radical is located on cysteine C, and the sulfur is lost.…”
Section: Introductionmentioning
confidence: 99%